IMPLEMENTASI STANDAR PROSES PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR SWASTA TERPADU BANI RAUF KABUPATEN GOWA - Ilyas Ismail, Muh.; Henriana Hasan, Andi (Universitas Islam Negeri Alauddin Makassar, 2022)
The aims of this study were to: (1) describe the objective conditions of the standard process implementation at the Bani Rauf Integrated Private Elementary School, Kab. Gowa (2) describes the obstacles to implementing process standards at the Bani Rauf Integrated Private Elementary School, Kab. Gowa and how to solve it. (3) describes the results of the implementation of the standard process in the class III PAI subject at the Bani Rauf Integrated Private Elementary School, Kab. Gowa. This research is a qualitative research with inductive qualitative methods included in the field research category. The approach used is a normative theological approach, a pedagogical approach, a psychological approach, a sociological approach. The data analysis used is data reduction. , Data Display (Data Presentation), and Data Verification (drawing conclusions). The results obtained in this study indicate that: (1) The objective conditions of the implementation of process standards at the Bani Rauf Integrated Private Elementary School, Somba Opu District, Gowa Regency include planning the learning process, implementing the learning process, assessing the learning process, and supervising the learning process. 2) obstacles to implementing process standards at the Bani Rauf Integrated Private Elementary School, Kab. Gowa and how the solution is that students sometimes experience difficulties in the learning process taking place at the Bani Rauf Integrated Private Elementary School, Somba Opu District, Gowa Regency. Factors that influence the learning process on Islamic Religious Education subjects at the Bani Rauf Integrated Private Elementary School, Somba Opu District, Gowa Regency include parents, the environment, the students themselves, teachers, methodology, facilities and infrastructure, and curriculum. While the supporting factors are teachers also try to provide additional lessons or hold lessons in the afternoon, and the provision of teaching aids and good cooperation between school principals, teachers and parents of students in Islamic Religious Education learning activities, 3) The results of the implementation of the standard process in PAI class III subjects at the Bani Rauf Integrated Private Elementary School Kab. Gowa, namely the learning process system for Islamic Religious Education at the Bani Rauf Integrated Private Elementary School, Somba Opu District, Gowa Regency which includes aspects of procuring learning tools and learning procedures. Teachers are required to operate learning tools, especially the syllabus and lesson plans as a reference or learning guide so that the implementation of learning is effective and efficient, thus encouraging the achievement of student learning achievements. It can be seen the difference between before the standard process is applied in accordance with the procedure, students are not optimal in receiving lessons compared to after the standard process is applied in accordance with the regulations, student learning outcomes have reached the graduation standard